The Role of Food System Planning in Facilitating Local Food Procurement for Schools - Blomley, Elina; Soma, Tammara; Callihoo, Christine; Han, Richard; Páez-Varas, Claudia; Bodnar, Chris; Li, Belinda (Canadian Planning and Policy / Aménagement et politique au Canada, 2023)
Farm to School (F2S) programs seeks to connect students with their local food system and community. Providing local food to schools, however, relies on the continuity of local food production in British Columbia (B.C.), as well as the capacity and willingness of farmers to support this “alternative market.” Planners have an important role to play in supporting farmers’ ability to sustain local food systems. At the provincial level, planning for farmland preservation through the Agricultural Land Reserve has helped to secure some of the farmland needed to support local food production into the future. However, preserving farmland is only one part of the solution to sustain local food systems. Drawing upon key informant interviews (n=21), this paper identifies planning-related barriers and opportunities for local food procurement in schools. This research emphasizes the invaluable roles that farmers, government, and planners can play in reimagining a just and sustainable food system transition.